Cross-linking multiwall carbon nanotubes using PFPA to build robust, flexible and highly aligned large-scale sheets and yarns. (12th February 2016) - Inoue, Yoku; Nakamura, Kazumichi; Miyasaka, Yuta; Nakano, Takayuki; Kletetschka, Gunther
Abstract: Multi-walled carbon nanotube (CNT) structures, including unidirectionally aligned sheets and spun yarns, were fabricated by direct dry-spinning methods from spinnable CNT arrays. We improved the mechanical properties of the CNT structures. CNTs were tailored in sheets and yarns using perfluorophenyl azide (PFPA) as a binding agent. The azide group of PFPA bonds to graphene crystal surfaces under UV radiation exposed for 1 h. For the CNT sheet, Young's modulus increased from 1.6 to 32.9 GPa and tensile strength increased from 35.9 MPa to 144.5 MPa. For the CNT yarns Young's modulus increased from 29.5 to 78.0 GPa and tensile strength increased from 639.1 to 675.6 MPa. With this treatment, the CNT sheets became more robust and more flexible materials. Since cross-linking of CNTs by PFPA is a simple and rapid process, it is suitable for fabrication of enhanced CNT materials.